Current concepts in CT Diagnosis and TNM-8 staging of Lung Cancer - Nikolova, Sonja (My University, 2023)
Regardless of the colossal efforts in lung cancer treatment, the majority of patients will present at an advanced stage when any curative treatment will no longer be an option. The overall 5-year survival for all tumor stages is disturbingly low at 15%, and lung cancer is the leading cause of cancer-related deaths for both genders worldwide. Early diagnosis as well as appropriate radiological staging is of utter importance for patients with early-stage lung cancer that can greatly benefit from timely treatment. The current 8th revision of tumor, node, metastasis (TNM) staging system accepted by The International Association for the Study of Lung Cancer (IASLC) and the American Joint Committee on Cancer (AJCC) was published in January, 2017, and the edition has committed some major alternations, including modification of the T classification based on 1 cm increment, down staging of the T descriptor disregarding its distance from carina (T2), integrating total and partial atelectasis/pneumonitis into the same T category (T2), upstaging diaphragmatic invasion to T4, new classification concepts of adenocarcinoma in situ and minimally invasive adenocarcinoma for pure and part-solid ground-glass nodules, and further division of extra thoracic metastasis into M1b and M1c based on their number and location. There is an agreement for some ambiguous conditions, such as the classification of Pancoast tumor based on its invasion depth, as well as categorization of various sites of pulmonary involvement. The IASLC Staging Project has provided evidence based recommendations for the TNM Classification for Thoracic Cancers in the last 20 years. The upgraded 9th edition of the TNM will be published on January 1, 2024 and will consider new data elements, including genetic biomarkers, protein alterations, and copy number alterations. In order for a radiologist to present an accurate clinical stage of lung cancer using consistent standards introduced in the 8th edition of the TNM Lung Cancer Staging System, it is important to acknowledge the prospective difficulties and limitations of imaging interpretation.
Keywords: TNM stage; lung cancer; T descriptor; N descriptor; M descriptor